Tingkat Kepuasan Masyarakat terhadap Kinerja Karyawan di Bank Aceh Syariah Cabang Meulaboh - Firdayanti, Laisa; Rusdi, Rusdi (Medan Resource Center, 2023)
This article aims to discuss the level of community satisfaction with employee performance at Bank Aceh Syariah Meulaboh Branch. This research is considered important to see how employee performance is significantly influenced by community satisfaction which significantly drives the performance itself. The development of Bank Aceh Syariah in serving customers can actually be an indicator to see how Bank Aceh Syariah employees carry out the process of providing financial services. So far, Bank Aceh Syariah, which is the pride of the people of Aceh Province, has made many improvements step by step in terms of service. This study took place in West Aceh District with 102 research respondents who were collected as samples. Broadly speaking, all questions indicate that there is an influence of community satisfaction on employee performance and can be a reference for the management of Bank Aceh itself to pay attention to responses from customers in the process of improving the company's internal performance.